Solve for x 2(x-3)-6=0

Math
2(x-3)-6=0
Simplify 2(x-3)-6.
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
2x+2⋅-3-6=0
Multiply 2 by -3.
2x-6-6=0
2x-6-6=0
Subtract 6 from -6.
2x-12=0
2x-12=0
Add 12 to both sides of the equation.
2x=12
Divide each term by 2 and simplify.
Tap for more steps…
Divide each term in 2x=12 by 2.
2×2=122
Cancel the common factor of 2.
Tap for more steps…
Cancel the common factor.
2×2=122
Divide x by 1.
x=122
x=122
Divide 12 by 2.
x=6
x=6
Solve for x 2(x-3)-6=0

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top